Green Synthesis of Magnetite Nanoparticles for the Photocatalytical Degradation of Cationic Dye - Pant, Chet Raj; (Rajbhandari), Armila Nyachhyon (Journal of Nepal Chemical Society, 2025)
Green synthesis of magnetite nanoparticles being cost effective and ecofriendly treatment technique, is gaining importance in these days. Aim of the study is to synthesize magnetite nanoparticles and to evaluate its photocatalytical efficiency in treating cationic dye solution. The magnetite (Fe3O4) has been successfully synthesized in laboratory by thermal process followed by co-precipitation technique using FeSO4.7H2O as precursor material. Here, coriandrum sativum extract act as a capping agent to confine the size and to control the over-growth of the material. Thus prepared materials were characterized by using X-Ray diffraction (XRD). The peak at 29.6, 35.6, 43.83, 54.35, 2θ degrees indicated the crystalline inverse cubic spinal structure of magnetite. The average crystallite size of particles was found to be 57.54 nm demonstrating nano size of the material.  Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) has been used to find surface functional group and morphological study. The FTIR bands clearly showed the bands of Fe-O, and O-H at 577 cm-1 and 3500 cm-1 respectively. The sharp peak UV peak at 361 nm indicated the complexation of iron with phenolic constituent of plants extract. The other absorption peaks at 334, 383 and 387 nm were due to presence of other components in plant extract. Thus synthesized nanoparticle has been used as photocatalyst for the photocatalytical degradation of methylene blue (MB) dye under UV light irradiation. The results revealed that at pH 11, 96.02 % of the MB dye has been degraded within 4 hrs of UV light irradiation in presence of magnetite (Fe3O4) catalyst and 2 mL H2O2.